Investigation of magnetorheological fluid-based finishing process for improving the functional performance of hydraulic cylinder. (June 2022) - Paswan, Sunil Kumar; Aggarwal, Ankit; Singh, Anant Kumar
A cylindrical barrel is a crucial part of the hydraulic cylinder that enables the mechanical system to apply high power to get the desired work, such as moving, pressing, and lifting the high-weight materials, done. The smoothness in the functioning of the machinery performing the tasks of these kinds is directly linked with the quality of the interior surface finish of the hydraulic cylinder's cylindrical barrel. In this study, the inside surface of a real-time hydraulic cylinder's barrel is completed to achieve a fine finish. The cylindrical barrel of the hydraulic cylinder with a fine-finished internal surface causes the related machinery to consume less power to get the desired work done. The smooth functioning of different kinds of machinery is affected by the level of internal surface finish of the cylindrical barrel of the hydraulic cylinder. For investigating the best parameters of the magnetorheological finishing process over the interior surface of the hydraulic cylinder's cylindrical barrel, the response surface methodology has been used. Through 60 min of magnetorheological-finishing using optimal finishing conditions, the final surface roughness is achieved up to 40 nm from 380 nm of initially honed roughness. Also, the improvement in dimensional and geometric accuracies has been analysed through surface waviness and circularity measurement before and after the magnetorheological-finished surface. Through the scanning electron microscopy tests, the enhancement in surface consistency of the cylindrical barrel of the hydraulic cylinder's finished surface is analysed. The overall results demonstrate the significant importance of the rotating-magnetorheological honing process to fine finish the inside surface of the cylindrical barrel of the hydraulic cylinder.